Galeria Denise René : Art Concret. - Cieslinska, Nawojka; Czartoryska, Urszula; Przybos, Julian; Ptaszkowska, Anka; René, Denise; Stanislawski, Ryszard (Lódz : Muzeum Sztuki, 1997)
Albers, Josef ; Arp, Hans (Jean) ; Bill, Max ; Boto, Martha ; Bury, Pol ; Cahn, Marcelle ; Claisse, Geneviève ; Cruz-Diez, Carlos ; Delaunay, Sonia ; Demarco, Hugo ; van Doesburg, Theo ; Equipo 57 ; Fruhtrunk, Günter ; Gerstner, Karl ; Gorin, Jean ; Herbin, Auguste ; Heurtaux, André ; Jacobsen, Robert ; Kandinsky, Wassily ; Kassak, Lajos ; Kupka, Frantisek ; Le Corbusier ; Morellet, François ; Mortensen, Richard ; Nemours, Aurélie ; Parc, Julio Le ; Schoffer, Nicolas ; Seuphor, Michel ; Sobrino, Francisco ; Soto, Jesus Rafael ; Taeuber-Arp, Sophie ; Vasarely, Victor
biografie
Galeria Denise René : Art Concret /Galerie Denise René : Sztuka konkretna, Muzeum Sztuki, Lódz, 9.5.1997 - 14.7.1997
Frans & Pools
boek